The Gut Microbiota: A Novel Player in Autoimmune Hepatitis - Cheng, Zilu; Yang, Ling; Chu, Huikuan (Frontiers in Cellular and Infection Microbiology, 2022)
Autoimmune hepatitis (AIH) is a chronic immune-mediated liver disease that is distributed globally in all ethnicities with increasing prevalence. If untreated, the disease will lead to cirrhosis, liver failure, or death. The intestinal microbiota is a complex ecosystem located in human intestine, which extensively affects human physiological and pathological processes. With more and more in-depth understandings of intestinal microbiota, a substantial body of studies has verified that intestinal microbiota made great contributions to a variety of digestive system diseases, including alcohol-associated liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD), but only several studies have paid attention to evaluate the relationship between AIH and the intestinal microbiota. Currently, AIH pathogenesis is not fully elucidated, but some studies have indicated that intestinal microbiota putatively made great contributions to the occurrence and the development of AIH by triggering several specific signaling pathways, altering the metabolism of intestinal microbiota，as well as modulating immune response in the intestine and liver. By collecting the latest related literatures, this review summarized that there is an increase in the abundance of aerobic bacteria in patients with AIH and AIH model mice, and there were alterations of luminal metabolites and immune responses, including decreased short-chain fatty acids (SCFAs), increased pathogen associated molecular patterns (PAMPs), imbalanced regulatory T (Treg)/Th17 cells, follicular regulatory T (TFR)/ follicular helper T (TFH) cells, and activated natural killer T (NKT) cells. These alterations participate in the onset and the progression of AIH via multiple mechanisms. Therefore, some therapeutic methods based on restoration of intestinal microbiota composition, including probiotics and fecal microbiota transplantation (FMT), as well as targeted intestinal microbiota-associated signaling pathways, confer novel insights into the treatment for AIH patients.